High‐throughput proteomics of breast cancer interstitial fluid: identification of tumor subtype‐specific serologically relevant biomarkers. Issue 2 (4th January 2021) - Terkelsen, Thilde; Pernemalm, Maria; Gromov, Pavel; Børresen‐Dale, Anna‐Lise; Krogh, Anders; Haakensen, Vilde D.; Lethiö, Janne; Papaleo, Elena; Gromova, Irina
Abstract : Despite significant advancements in breast cancer (BC) research, clinicians lack robust serological protein markers for accurate diagnostics and tumor stratification. Tumor interstitial fluid (TIF) accumulates aberrantly externalized proteins within the local tumor space, which can potentially gain access to the circulatory system. As such, TIF may represent a valuable starting point for identifying relevant tumor‐specific serological biomarkers. The aim of the study was to perform comprehensive proteomic profiling of TIF to identify proteins associated with BC tumor status and subtype. A liquid chromatography tandem mass spectrometry (LC‐MS/MS) analysis of 35 TIFs of three main subtypes: luminal (19), Her2 (4), and triple‐negative (TNBC) (12) resulted in the identification of > 8800 proteins. Unsupervised hierarchical clustering segregated the TIF proteome into two major clusters, luminal and TNBC/Her2 subgroups. High‐grade tumors enriched with tumor infiltrating lymphocytes (TILs) were also stratified from low‐grade tumors. A consensus analysis approach, including differential abundance analysis, selection operator regression, and random forest returned a minimal set of 24 proteins associated with BC subtypes, receptor status, and TIL scoring. Among them, a panel of 10 proteins, AGR3, BCAM, CELSR1, MIEN1, NAT1, PIP4K2B, SEC23B, THTPA, TMEM51, and ULBP2, was found to stratify the tumor subtype‐specific TIFs. In particular, upregulation of BCAM and CELSR1 differentiates luminal subtypes, while upregulation of MIEN1 differentiates Her2 subtypes. Immunohistochemistry analysis showed a direct correlation between protein abundance in TIFs and intratumor expression levels for all 10 proteins. Sensitivity and specificity were estimated for this protein panel by using an independent, comprehensive breast tumor proteome dataset. The results of this analysis strongly support our data, with eight of the proteins potentially representing biomarkers for stratification of BC subtypes. Five of the most representative proteomics databases currently available were also used to estimate the potential for these selected proteins to serve as putative serological markers. Abstract : Analysis of breast tumor interstitial fluids (TIF) may help identify protein biomarkers that are secreted in the circulation. Following extraction of breast tumor TIF, LC‐MS/MS TMT labeled proteomics, and bioinformatic analyses we identified a panel of secreted protein biomarkers. Experimental and computational validation using tissues and external datasets, respectively, indicated the potential of this biomarker panel for breast cancer subtype stratification.